Design of a web based library information system at Bahrul Ulum Islamic middle school - Winarti, Wiwin; Aqhilla Qhoriza (SEAN Institute, 2024)
At this time, information systems play an important role in improving business and educational efficiency. In the era of globalization, education needs to adapt to changes in thinking patterns and needs that are fast-paced, practical and precise. The presence of information technology is able to serve these needs. At Bahrul Ulum Islamic Middle School, library data management is still done manually, causing data inaccuracies, loss of book information, difficulty tracking loan status, and making reports that takes time and is therefore inefficient. The aim of this research is to design a Web-Based Library Information System Application at Bahrul Ulum Islamic Middle School. Data collection was carried out through literature study, observation and interviews. The software development method used is Rapid Application Development (RAD). By designing a web-based library information system application, it is hoped that it can improve the quality and performance of the application, minimize errors, ensure efficient use and improve services at the Bahrul Ulum Islamic Middle School library.